REGIONAL GROUPING AND HUMAN DEVELOPMENT INEQUALITY IN WEST NUSA TENGGARA: AN EMPIRICAL STUDY USING HIERARCHICAL CLUSTER AND DAVIES BOULDIN INDEX - Hesikumalasari, Hesikumalasari; Adhar, Adhar; Husna Ainu Syukri, Siti (Universitas Islam Negeri Mataram, 2025)
This study analyzes the spatial grouping of cities and districts in West Nusa Tenggara (NTB), Indonesia, based on indicators of the Human Development Index (HDI). Using secondary data from the NTB Central Bureau of Statistics for 2022, four HDI components, which include life expectancy at birth, expected years of schooling, mean years of schooling, and adjusted per capita expenditure, were employed as clustering variables. A hierarchical cluster analysis with various linkage methods, including average, single, complete, centroid, median, and Ward methods, was applied to classify the ten cities and districts. The optimal number of clusters was determined using the Davies–Bouldin Index (DBI). The results reveal that the lowest DBI value (0.4573) was obtained through the single linkage method, indicating the formation of three optimal clusters. The first cluster includes West Lombok and West Sumbawa Regencies, the second cluster consists of Central Lombok, East Lombok, Sumbawa, Dompu, Bima, North Lombok, and Bima City, while the third cluster contains only Mataram City. The findings highlight regional disparities in HDI performance across NTB and suggest that human development programs should be tailored according to the characteristics of each cluster to ensure more equitable progress among regions. KEYWORDS: Human Development Index, cluster analysis, regional disparities, West Nusa Tenggara, hierarchical clustering.